On the generic and specific identity of the holotype of Rana hymenopus Boulenger 1920 (Amphibia: Anura: Pyxicephalidae) - Clarke, Barry T.; Poynton, John C. (Zootaxa, 2012)
The proposal by Tarrant et al. (2008) to refer the holotype of Rana hymenopus Boulenger 1920 to Amietia fuscigula isrejected. The holotype has been re-examined and, using external morphological and osteological characters, found to begenerically and specifically distinct from A. fuscigula. We refer the holotype to the genus Strongylopus Tschudi as a validspecies, S. hymenopus. The provenance of this specimen is established as South Africa, presented to the British Museumby Sir Andrew Smith, accessioned in 1858, and currently recognised in the Natural History Museum, London as Bouleng-er’s Rana hymenopus holotype. Some consequences of retrieving the name hymenopus from the synonymy of A. fuscigula are noted.